2016
DOI: 10.1097/ijg.0000000000000378
|View full text |Cite
|
Sign up to set email alerts
|

Regression Analysis of Optical Coherence Tomography Disc Variables for Glaucoma Diagnosis

Abstract: Purpose To report diagnostic accuracy of optical coherence tomography (OCT) disc variables using both time-domain (TD) and Fourier-domain (FD) OCT, and to improve the use of OCT disc variable measurements for glaucoma diagnosis via regression analyses that adjust for optic disc size and axial length-based magnification error Design Observational, cross-sectional Participants 180 normal eyes of 112 participants and 180 eyes of 138 participants with perimetric glaucoma from the Advanced Imaging for Glaucoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…The present study also showed a moderate positive correlation between GSS2 and the cup-to-disc ratio, which is consistent with that of Richter et al, 18 who reported that the disc rim area and vertical CDR had very high diagnostic accuracy and could complement additional OCT measurements for the diagnosis of glaucoma.…”
Section: Discussionsupporting
confidence: 93%
“…The present study also showed a moderate positive correlation between GSS2 and the cup-to-disc ratio, which is consistent with that of Richter et al, 18 who reported that the disc rim area and vertical CDR had very high diagnostic accuracy and could complement additional OCT measurements for the diagnosis of glaucoma.…”
Section: Discussionsupporting
confidence: 93%